Konstruksi Kelembagaan Daerah Khusus Jakarta - Pramono, Sidik (Neolectura, 2024)
After the State Capital City Law relocated Indonesia's capital to the Nusantara region in East Kalimantan, Jakarta's status changed to that of a special region. This change was ratified with the approval of the Special Region Provincial Law for Jakarta during the Plenary Session of the People's Representative Council on March 28, 2024. Jakarta's unique efforts to become a progressive and sustainable global city necessitate coordination and integration with neighbouring areas, including those within the Jakarta Agglomeration Zone. This study utilises a qualitative approach with a descriptive analysis methodology, gathering data through documentary research involving document collection and analysis. Data analysis techniques included data reduction, display, discussion, and conclusion drawing, with data validity assessed through triangulation. The research aims to recognise the necessity for new institutions to manage Jakarta as a special region and ensure their support for Jakarta's transformation into a globally significant national economic hub, including its surrounding areas. The research findings emphasise the importance of these new institutions, as the capital city area and its supporting regions are no longer considered manageable separately, exacerbated by regulatory differences between central and regional levels.